Management Of Early Children's Learning With Steam Loading With Loose Parts at RA Ummatan Wahidah Curup - Cucu Rahayu; Jumira Warlizasusi; Fakhruddin Fakhruddin (Universitas Bengkulu, 2022)
Implementation of Early Childhood Education faces many problems in the learning system. Just as the lack of creativity and progress of educators, as well as educational game devices that are less supportive, so the learning system does not encourage the ability of students to innovate and think higher. The research objectives are learning management, and implementation of STEAM content made from Loose Parts. The research used descriptive qualitative method. Research data sources include primary and secondary sources. The research instrument, data collection using observation, interview, and documentation techniques. Then the data is analyzed through the stages of data collection, data reduction, data display, and conclusions. The results of this study that the management of STEAM content learning with Loose Parts : planning the form of learning for RPPS, RPPM, RPPH, preparing Loose Parts . Organizing teaching tasks, teachers allocate learning materials. Implementation starts from the introduction, core activities, closing activities. Assessment in the form of performance, observation, conversation. Implementation of early childhood learning with STEAM content made from Loose Parts : applying all stages of play by paying attention to playing strategies, cleaning, storing things, strategies to develop early childhood creativity. The activity plan is adapted to the needs of the child and takes into account the principles of PAUD learning